2022
DOI: 10.3390/su142416375
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Extrinsic and Intrinsic Motivations in the Relationship between Community Leadership and Social Capital in Rural Malaysia

Abstract: (1) Background: Social capital linking, bridging, and bonding have become fascinating options for sustainable development in rural Malaysia. (2) Objective: The aims of this research were (i) to evaluate how leadership styles affect the social capital in rural Malaysia, and (ii) to examine the moderating role of motivation in enhancing these relationships. (3) Methods: The researchers utilized a quantitative approach to analyze data collected through a self-administered survey involving 190 members of the Villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Extrinsic rewards are material benefits acquired via performance at work, such as compensation and promotions (Badubi, 2017). As a result, a successful extrinsic compensation system is required to improve staff performance and efficiency (Rami et al, 2022).…”
Section: Concept Of Motivationmentioning
confidence: 99%
“…Extrinsic rewards are material benefits acquired via performance at work, such as compensation and promotions (Badubi, 2017). As a result, a successful extrinsic compensation system is required to improve staff performance and efficiency (Rami et al, 2022).…”
Section: Concept Of Motivationmentioning
confidence: 99%
“…In this section, theories that underpin the concept of academic engagement are explored, offering a profound understanding of its dimensions and determinants. In this theoretical review, we can relate the self-determination theory that explores human motivation and psychological needs that influence behavior and participation in activities, including academic domain (Md-Rami et al, 2022). Decy and Ryan on 80s decade, asserted that this theory has become a fundamental pillar for understanding the relationship between motivation and academic engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Jamali et al (2022) illustrated a positive impact of laissez-faire leadership on faculty performance in academic institutions. Md Rami et al (2022) found that laissez-faire leadership is beneficial to social capital.…”
Section: Introductionmentioning
confidence: 99%